A Clinicopathological Study of Aural Polyps: A Retrospective Analysis in a Tertiary Care Hospital - Kothegala Chandrashekaraiah Prasad; Gopinath Indu Varsha; Kouser Mohammadi; Arjun Gupta; Diana Ann Jose (International Archives of Otorhinolaryngology, 2024)
Introduction Aural polyps are a misnomer. Any lesion can present as a mass in the external auditory canal. Aural polyps are proliferation of the granulation tissue due to long standing inflammatory process with associated otalgia and otorrhea.